2017
DOI: 10.5194/aab-60-385-2017
|View full text |Cite
|
Sign up to set email alerts
|

Three-step in vitro maturation culture of bovine oocytes imitating temporal changes of estradiol-17<i>β</i> and progesterone concentrations in preovulatory follicular fluid

Abstract: Abstract. The objective of the article is to evaluate the effect of three-step in vitro maturation (IVM) culture system imitating estradiol-17β (E 2 ) and progesterone (P 4 ) concentrations in preovulatory follicles on in vitro bovine embryo production. The cumulus-oocyte complexes (COCs) were collected from follicles (2 to 8 mm in diameter) of bovine ovaries obtained from a local slaughterhouse. For IVM, the COCs were cultured for 22 h in a three-step system: (1) culture in medium 199, containing 700 ng mL −1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…The authors concluded that supplementation with P 4 during culture does not improve cleavage of presumptive zygotes, embryo development, and blastocyst rate. Matsuo et al (78) used a 3-step oocyte culture system that mimicked temporal physiological changes in E 2 and P 4 , and reported that the treatment enhanced in vitro embryo development reflected as a greater blastocyst formation rate. Reis et al (79) cultured zygotes in the following groups (concentrations in μg/mL): control, 1 E 2 + 100 P 4 , 1 E 2 , and 100 P 4 .…”
Section: Evidence On the Effect Of Hormonesmentioning
confidence: 99%
“…The authors concluded that supplementation with P 4 during culture does not improve cleavage of presumptive zygotes, embryo development, and blastocyst rate. Matsuo et al (78) used a 3-step oocyte culture system that mimicked temporal physiological changes in E 2 and P 4 , and reported that the treatment enhanced in vitro embryo development reflected as a greater blastocyst formation rate. Reis et al (79) cultured zygotes in the following groups (concentrations in μg/mL): control, 1 E 2 + 100 P 4 , 1 E 2 , and 100 P 4 .…”
Section: Evidence On the Effect Of Hormonesmentioning
confidence: 99%
“…FF is an exudate of the blood serum and additionally contains growth factors and metabolic intermediates produced by the oocyte and somatic cells composing the follicle (Jiang et al, 2010;Sugiura, Pendola, & Eppig, 2005). Follicular somatic cells, more specifically the theca interna and mural granulosa cells, produce steroids, which are essential in sustaining oocyte and follicle development and survival and prepare the endometrium (Grupen & Armstrong, 2010;Matsuo et al, 2017;Okutsu, Itoh, Takahashi, & Ishizuka, 2010;Ting, Xu, & Stouffer, 2015). According to the two-cell type theory of ovarian steroidogenesis, theca cells convert cholesterol into progestins and androgens, while granulosa cells express FSHinduced aromatase (CYP19A1) to convert the androgens into 17β-estradiol (Liu & Hsueh, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…These effects suggest steroid concentrations during oocyte maturation in vitro are also important for oocyte developmental competency. Indeed, the addition of steroids in vitro has been shown to increase oocyte developmental competency and therefore represent another factor influencing the attainment of oocyte developmental competency in vitro (Ali & Sirard, 2002b;Aparicio et al, 2011;Matsuo et al, 2017;Soares et al, 2017;Younis et al, 1989). 1.3.14.4 Cholesterol In the follicle, mural granulosa cells synthesise steroids required for fertility (Hillier & Tetsuka, 1997;Hu et al, 2010;Li et al, 2000;Vanderhyden & Tonary, 1995).…”
Section: 3143mentioning
confidence: 99%